"Nothing About Me Without Me": An Interpretative Review of Patient Accessible Electronic Health Records - Jilka,SR; Callahan,R; Sevdalis,N; Mayer,EK; Darzi,A (Journal of Medical Internet Research, 2015)
BackgroundPatient accessible electronic health records (PAEHRs) enable patients to access and manage personalclinical information that is made available to them by their health care providers (HCPs). It is thought thatthe shared management nature of medical record access improves patient outcomes and improves patientsatisfaction. However, recent reviews have found that this is not the case. Furthermore, little research hasfocused on PAEHRs from the HCP viewpoint. HCPs include physicians, nurses, and service providers.ObjectiveWe provide a systematic review of reviews of the impact of giving patients record access from both apatient and HCP point of view. The review covers a broad range of outcome measures, including patientsafety, patient satisfaction, privacy and security, self-efficacy, and health outcome.MethodsA systematic search was conducted using Web of Science to identify review articles on the impact ofPAEHRs. Our search was limited to English-language reviews published between January 2002 andNovember 2014. A total of 73 citations were retrieved from a series of Boolean search terms including“review” with “patient access to records”. These reviews went through a novel scoring system analysiswhereby we calculated how many positive outcomes were reported per every outcome measureinvestigated. This provided a way to quantify the impact of PAEHRs.Results1 1 2 1112Ten reviews covering chronic patients (eg, diabetes and hypertension) and primary care patients, as well asHCPs were found but eight were included for the analysis of outcome measures. We found mixedoutcomes across both patient and HCP groups, with approximately half of the reviews showing positivechanges with record access. Patients believe that record access increases their perception of control;however, outcome measures thought to create psychological concerns (such as patient anxiety as a result ofseeing their medical record) are still unanswered. Nurses are more likely th